Kitâb al Muḥâwarah al Hadîthah Al Juz’u al Awwal: Taḥlîl al Muḥtawa inda Naẓahriyyah Nâṣir Abd al Ghâli - Safitri, Intan; Thohir, Muhammad; Hanifah, Umi (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Objective- This study aims to find out whether the book Muhawaratul Haditsah first chapter complies with the four criteria for teaching materials put forward by Abdul Ghali and whether this book is suitable for learning Arabic.  Design / Methodology / Qualitative- This research uses the documentation method or what is often referred to as library research or library research with a content analysis approach. What was used to collect data and information in this study were documents related to research and analysis of the textbooks examined by researchers.  Findings- This research shows that the book "Muhawarotil Haditsah" first chapter as a whole focuses on the contents of the book learning about Islamic culture and learning adab or noble character, this aims so that students can learn how to be a Muslim and socialize well in their environment both at school and at home. And although the four criteria for teaching materials put forward by Abdul Ghali are not one hundred percent fulfilled by this book, this book is very feasible to use, especially for students who are in Islamic boarding schools.  Research Limitations/Implications- In this study, the researcher focused on researching or analyzing the contents of the book "Muhawarotul Haditsah" first chapter using the basis of the subject matter proposed by Nasir Abdul Ghali. Namely, the basis of culture, psychology, language and education.